2020
DOI: 10.1002/cbf.3546
|View full text |Cite
|
Sign up to set email alerts
|

Silence of TPPP3 suppresses cell proliferation, invasion and migration via inactivating NF‐κB/COX2 signal pathway in breast cancer cell

Abstract: Malignant phenotypes are leading causes of death in patients with breast cancer (BC). Previously, it has been proved that tubulin polymerization promoting protein 3 (TPPP3) participates in cell progressions in several human cancers. Little is known about the functions of TPPP3 in BC. Herein, we detected the expression of TPPP3 in 54 clinical BC tissues and two BC cell lines by immunohistochemistry and Western blot. CCK‐8, wound healing, colony formation and Transwell assays were used to assess cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The mRNA expression levels of TPPP3 from the Oncomine database were significantly elevated in colorectal carcinoma and invasive ductal breast carcinoma ( Figure 1(a-b) ), which is consistent with previous published results [ 9 , 11 ]. However, this study analyzed NPC datasets GSE12452, GSE53819 and GSE61218, and found the mRNA expression levels of TPPP3 in NPC tissues were significantly lower than those in normal nasopharyngeal tissues ( Figure 1(c-e) ).…”
Section: Resultssupporting
confidence: 92%
“…The mRNA expression levels of TPPP3 from the Oncomine database were significantly elevated in colorectal carcinoma and invasive ductal breast carcinoma ( Figure 1(a-b) ), which is consistent with previous published results [ 9 , 11 ]. However, this study analyzed NPC datasets GSE12452, GSE53819 and GSE61218, and found the mRNA expression levels of TPPP3 in NPC tissues were significantly lower than those in normal nasopharyngeal tissues ( Figure 1(c-e) ).…”
Section: Resultssupporting
confidence: 92%
“…Further, the in vitro experiment demonstrated that RSRC2 could inhibit the MDA-MB-231 cells and MDA-MB-453 cells clonogenic ability, adhesion, migration and invasion ability. The transcriptome array data analysis identified differentially expressed genes in the MDA-MB-231 shRSRC2 cells and control cells and identified SCIN, IL6, CXCL8, CXCL1, PTGS2, IL1B, NOS3, ICAM1, moesin and DCAF6, which were reported to be involved in cell proliferation, migration and cell adhesion [ 15 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The intersection set analysis of the bioinformatics database and transcriptome array data identified six common genes, FSTL1, GDF15, IQSEC2, KDM3A, LTC4S and TCTEX1D4, in which most of them were involved in tumor cell proliferation and growth [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…by different ways. But in breast cancer 27 and non-small cell lung cancer 9 , there was a carcinogenic effect. Our research found that TPPP3 was an oncogene in glioma cells, which promoted the malignant biological behavior of glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%